Effects of late sowing on soybean yields and yield components in southwestern Japan. (2nd October 2018) - Kawasaki, Yohei; Yamazaki, Ryo; Katayama, Katsuyuki
ABSTRACT: Soybean production in southwestern Japan tends to be unstable owing to wet soils during the rainy season. Although late sowing after the rainy season can avoid excess water, information on its yield potential is limited. The objective of this study was to reveal the effect of late sowing on yields and yield components of new soybean cultivars developed for warm regions. The experiment was conducted in 2016 and 2017 in Fukuyama, Hiroshima, Japan. Upland fields converted from paddy fields with a subirrigation system were planted in June (normal) or July (late sparse or late dense). Lodging was prevented with a net. The effects of late sowing and dense treatment were analyzed in relation to solar radiation use. In 2016, differences in yield among cultivars and among environments were not significant. In 2017, yield was significantly reduced following late sparse sowing. The total aboveground dry matter at maturity was correlated with total solar radiation intercepted ( r  = 0.76) but not with radiation use efficiency ( r  = 0.47). Late sowing increased harvest index (HI) significantly from 0.464 to 0.571 in 2016 and from 0.524 to 0.585 in 2017, but density had no significant effect. The changes in HI were correlated with stem dry weight ( r  = −0.80 in 2016 and r  = −0.79 in 2017) rather than seed yield ( r  = 0.08, n.s. in 2016 and r  = 0.19, n.s. in 2017). Thus, under irrigation, late dense sowing might stabilize yield in southwestern Japan because of higher HI. Abbreviations: DM: dry matter; FOEAS: farm-oriented enhancing aquatic system; HI: harvest index; RUE: radiation use efficiency